1983
DOI: 10.1901/jeab.1983.39-293
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state Performance on Fixed‐, Mixed‐, and Random‐ratio Schedules

Abstract: Three groups of rats pressed a lever for milk reinforcers on various simple reinforcement schedules (one schedule per condition). In Group M, each pair of conditions included a mixed-ratio schedule and a fixed-ratio schedule with equal average response:reinforcer ratios. On mixed-ratio schedules, reinforcement occurred with equal probability after a small or a large response requirement was met. In Group R, fixed-ratio and random-ratio schedules were compared in each pair of conditions. For all subjects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
96
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 16 publications
13
96
0
Order By: Relevance
“…Previous studies ofIRTs and PRPs in FR schedules have reported that PRPs increase as a function of the FR, but that IRTs of less than 1 sec remain relatively constant (Felton & Lyon, 1966;Mazur, 1983). Those studies, however, were all performed in an open economy: the animals were food deprived, earned some portion of their food within a short experimental session, and were consequently returned to their home cages where supplemental food was provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies ofIRTs and PRPs in FR schedules have reported that PRPs increase as a function of the FR, but that IRTs of less than 1 sec remain relatively constant (Felton & Lyon, 1966;Mazur, 1983). Those studies, however, were all performed in an open economy: the animals were food deprived, earned some portion of their food within a short experimental session, and were consequently returned to their home cages where supplemental food was provided.…”
Section: Discussionmentioning
confidence: 99%
“…A word of caution,however, should be addedconcerning IRTs. Although Mazur (1983), with reference to his IRT distributions, notesthat "there was no tendency for the peaks to shift toward longer IRTs as ratio size increased" (p. 297), there was an increase in "long" IRTs (lRTs greater than 1 sec) with FR size. Such long IRTs represented lessthan 10% of all IRTs in the Mazurstudy, and it is probably true that the median IRT, as a resistant measureof centraltendency (Hartwig & Dearing, 1979), wouldbe relatively unaffectedby longIRTs in the present study.…”
Section: Demand Curvesmentioning
confidence: 97%
“…Equation 3 provides a good account of the behavior of pigeons on ratio schedules, both on VR schedules with the coupling coefficient defined by Equation 2 (e.g., Green, Kagel, & Battalio, 1982;Mazur, 1983), and on fixed-ratio (FR) schedules (e.g., Powell, 1968) using the appropriate coupling coefficient. In particular, changes in the amount or quality of the reinforcer have the expected effects on both the shape of the response rate functions and on the corresponding values of a (see Figure 2, from Bizo & Killeen, 1997).…”
Section: Model and Predictionsmentioning
confidence: 99%
“…The FR variable most often investigated is ratio size. As FR size increases, the length of the postreinforcement (sometimes called preratio) pause (PRP) also increases whether pigeons (Felton & Lyon, 1966;Powell, 1968) or rats (Mazur, 1983) are subjects. Response rates, as a function of this same parameter, also have been reported.…”
mentioning
confidence: 99%
“…It is more difficult to locate studies that have manipulated ratio size in variable-ratio (VR) or random-ratio (RR) schedules, as Mazur (1983) has indicated. Priddle-Higson, Lowe, and Harzem (1976) examined changes in reinforcer magnitude and changes in VR size.…”
mentioning
confidence: 99%